GEOTHERMAL POTENTIAL ON SUMATRA FAULT SYSTEM TO SUSTAINABLE GEOTOURISM IN WEST SUMATRA - Hari Wiki Utama; Rahmi Mulyasari; Yulia Morsa Said (Engineering Faculty Universitas Lampung, 2021)
Sumatra Island is an island that is traversed an active ring of fire at Barisan Range which is related to the active Sumatra fault system and geothermal manifestations. It is associated with geothermal manifestations in Cubadak, Talu, Bonjol, and Rimbo Panti, Pasaman Regency, and West Pasaman Regency, West Sumatra Province, as an indication of a geothermal system connected to the Sumatra Fault System from the Sianok Segment and the Talamau Volcano Complex. Sustainable geotourism has become effective for sustainable development of geotourism, the geothermal energy direct utilization. The purpose of this study is to provide sustainable geotourism from geothermal potential in the fault system, taking into account aspects of village geotourism, ecotourism, ecoculture, and education. The methodology used in this study is to collect data on geothermal manifestations from regional geological maps and field observations in geothermal manifestation areas by considering sustainable geotourism. A simple model of sustainable geotourism is made. Study results indicate several locations of potential geothermal manifestations to be used as sustainable geotourism associated with the Sumatra Fault System and the Talamau Volcano Complex.